2018
DOI: 10.1002/jcp.27100
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol inhibits Erk1/2‐mediated adhesion of cancer cells via activating PP2A–PTEN signaling network

Abstract: Resveratrol, a natural polyphenol compound, has been shown to possess anticancer activity. However, how resveratrol inhibits cancer cell adhesion has not been fully elucidated. Here, we show that resveratrol suppressed the basal or type I insulin-like growth factor (IGF)-1-stimulated adhesion of cancer cells (Rh1, Rh30, HT29, and HeLa cells) by inhibiting the extracellular signal-regulated kinase 1/2 (Erk1/2) pathway. Inhibition of Erk1/2 with U0126, knockdown of Erk1/2, or overexpression of dominant-negative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 86 publications
0
5
0
Order By: Relevance
“…3 Treatment with resveratrol could decrease expression of miR-21 and finally decrease cancer cell survival; these events have been occurred after enhancing PTEN expression and blocking PI3K/AKT and mTOR pathways [94]. Also, resveratrol could decrease cancer cell survival and proliferation via inhibiting the ERK1/2 pathway [96,100] • fast, convenient online submission • thorough peer review by experienced researchers in your field • rapid publication on acceptance…”
Section: Discussionmentioning
confidence: 99%
“…3 Treatment with resveratrol could decrease expression of miR-21 and finally decrease cancer cell survival; these events have been occurred after enhancing PTEN expression and blocking PI3K/AKT and mTOR pathways [94]. Also, resveratrol could decrease cancer cell survival and proliferation via inhibiting the ERK1/2 pathway [96,100] • fast, convenient online submission • thorough peer review by experienced researchers in your field • rapid publication on acceptance…”
Section: Discussionmentioning
confidence: 99%
“…RAC1 is widely expressed in cells where it mediates cell remodeling, membrane transport, transcriptional regulation, cell growth, and development [35]. A previous study has reported that BCAR1 and RAC1 also regulate cell movement and adhesion [36]. Specifically, RAC1-mediated cell migration is initiated by BCAR1 [37].…”
Section: Discussionmentioning
confidence: 99%
“…At present, there are few studies indicating that the target of resveratrol may be associated with ERK1/2. When intracellular calcium is reduced to a certain limit, STIM1 protein is activated ( 50 ). This activation is mainly achieved through the phosphorylation of STIM1 protein at Ser575, Ser608 and Ser621, which are ERK1/2 target sites ( 51 ).…”
Section: Discussionmentioning
confidence: 99%